A New Chemical Mechanical Slurry for Polishing Yttrium Aluminium Garnet Material with Magnesium oxide, Sodium Metasilicate Pentahydrate and Zirconium Dioxide Abrasive Particles - Le Anh Duc; Pham Minh Hieu; Nguyen Minh Quang (Journal of Machine Engineering)
This work provided a new chemical-mechanical polishing mixture with MgO, sodium metasilicate pentahydrate, ZrO2 abrasive particles, and deionized water. With chemical-mechanical slurry (CMS) proposed for polishing yttrium aluminum oxide (Y3Al5O12) the surface reaction layer formed with significantly reduced hardness compared to other Y3Al5O12 materials, these products combine with MgO to form montmorillonites (3MgO–Al2O3–3SiO2–3Y2O3–5Al2O3). With this formation, the surface layer of Y3Al5O12 material becomes soft and is easily removed by ZrO2 abrasive particles under the influence of mechanical polishing, resulting in superfine surfaces generated from the proposed CMS model. The experimental results show that the surface quality with CMS proposed gives the surface quality with Ra = 0.471 nm along with the material removal rate 31 (nm/min). Surface quality is improved by 71% along with a superior material removal rate (increased by 287%) compared to silica slurry. The results show excellent polishing ability from CMS proposed for polishing Y3Al5O12 materials.